The Effect of Preoperative Nutritional Supports on Patients with Gastrointestinal Cancer: Prospective Randomized Study - Kirkil, Cuneyt; Bulbuller, Nurullah; Aygen, Erhan; Basbug, Murat; Ayten, Refik; Ilhan, Necip; Akbulut, Sami (H G E Update Medical Publishing S A, 2012)
Background/Aims: Malnutrition adversely affects the postoperative outcome of patients with gastrointestinal cancer. Therefore, the malnourished cancer patients are supported by enteral or parenteral nutrition. In this study, we aimed to investigate the effects of preoperative nutritional supports on total antioxidant capacity (TAC) in malnourished patients with gastrointestinal (GI) cancers. Methodology: Seventy-five malnourished patients with GI cancers and 25 patients with non-cancer surgical problems were included in the study. The dietary of cancer patients were supported with immune-enhancing enteral solution in group II or standard enteral solution in group III and with parenteral solution in group IV. Plasma TAC levels were measured prior and after nutritional support. Data were expressed as mmol Trolox eq./L. Results: The mean TAC levels of groups before treatment were 1.10 +/- 0.17, 0.92 +/- 0.19, 0.89 +/- 0.17 and 0.92 +/- 0.18, respectively. It was significantly higher in group I than others. The mean TAC levels of supported groups after treatment were 1.11 +/- 0.20, 1.08 +/- 0.21 and 1.09 +/- 0.27, respectively. Although there was a statistically significant increase in TAC after treatment in group II and III, it was not statistically significant in group IV. Conclusions: It was concluded that preoperative nutritional support with standard or immune-enhancing enteral solutions significantly increased TAC levels of malnourished patients with GI cancers.
Keywords: Clinical; Nutrition; Cancer; Total antioxidant capacity